Kecerdasan emosi dan kepuasan perkahwinan dalam kalangan Melayu bandar - Suzana Mohd Hoesni; Nor Ba’yah Abdul Kadir; Sarah Waheeda Muhammad Hafidz (Penerbit Universiti Kebangsaan Malaysia, 2018)
Emotional intelligence is one of the psychological aspects that are increasingly gaining attention among researchers who are interested in studying marital satisfaction. Emotional intelligence is frequently associated with the skills of an individual in being aware of their own emotions, and the emotion of others and being able to manage their own and other people’s emotions. Thus, this study aims to investigate emotional intelligence and marital satisfaction among urban Malays. This study applies the survey research design by using questionnaires aimed at gathering personal background information, and measuring emotional intelligence and marital satisfaction of respondents. A total of 578 Malay respondents who have been married for at least one year, Muslims and residing in Klang Valley voluntarily participated in this study. Overall, the results showed that emotional intelligence has a significant relationship with marital satisfaction. Emotional intelligence in this study which has been divided into two main components, self-management (r = 0.388, p < 0.01) and social skills (r = 0.285, p < 0.01**) showed a moderate significant relationship with marital satisfaction. This finding suggests the importance of emotional intelligence in helping to increase marital satisfaction among married couples. Suggestions for future researchers and helping professionals such as counsellors and therapists working with married couples are also discussed.